Integration of Tarbawi Hadith and Humanistic Educational Psychology in Holistic Education Development - Maslani Maslani; Tarsono; Ika Rostika; Saidah; Siti Vania Nuraida; Fazrin Syaibatul Hamdi Muzami (JIA (Jurnal Ilmu Agama), 2025)
This study examines the integration of intellectual and spiritual dimensions in education through the perspective of Hadith Tarbawi and Humanistic Educational Psychology. The main problem addressed in this research is the imbalance of modern education, which tends to prioritize cognitive intelligence while neglecting moral and emotional values. Using a qualitative approach with a library research method, this study explores primary sources from Hadith Tarbawi related to the education of reason (‘aql) and heart (qalb), as well as secondary sources discussing the theories of humanistic psychology proposed by Carl Rogers and Abraham Maslow. The findings indicate that both Hadith Tarbawi and Humanistic Educational Psychology share a similar vision of human development: the integration of intellect, emotion, and spirituality. The Hadith emphasizes purification of the soul (tazkiyah al-nafs) and moral balance, while humanistic psychology promotes empathy, freedom, and self-actualization. The integration of these two perspectives forms a comprehensive educational paradigm that nurtures intellectual excellence alongside moral and spiritual maturity. Thus, the study concludes that the balance between reason and heart is essential in shaping a holistic education system that fosters intelligent, ethical, and compassionate individuals. The findings of this study provide a conceptual contribution through an integrative mapping of tarbawi values and humanistic psychology, which may inform theoretical development and guide educators in designing learning practices that are more humanistic and value-driven.